Halal Tourism and Economic Resilience: A Systematic Bibliometric Review of the Literature - Ramadhan, Dicky Satria; Ramadhan, Eka Setya; Munawaroh, Asyifa Nur Laely (Indonesian Journal of Islamic Business and Economics (IJIBE), 2025)
The rapid growth of halal tourism as a global industry, fueled by the increasing Muslim population and high demand for sharia-compliant travel services, highlights the sector's significant potential for enhancing economic resilience. However, scientific studies directly linking halal tourism to economic resilience remain limited and poorly integrated. This study aims to address this gap by employing a bibliometric approach to map the development, trends, and emerging research themes in this field. Using a descriptive-quantitative method, secondary data were collected from the Google Scholar and Scopus databases, covering publications from 2015 to 2025. Analysis was conducted using Publish or Perish and VOSviewer software to trace patterns of author collaboration, keyword co-occurrence, top citations, and thematic evolution over time. The study's results indicate a significant upward trend in the number of publications, particularly after 2021, reflecting a growing academic interest in the role of halal tourism in fostering inclusive economic recovery. Bibliometric visualization reveals that initial research concentrated on socio-cultural aspects, such as religious tourism, MSMEs, and cultural heritage. However, in recent years, the focus has shifted toward macroeconomic issues, including regional economic resilience and demand-side strategies. These findings highlight the importance of incorporating halal tourism strategies into sustainable and resilient economic development policies, while also opening up avenues for further research in the future.